Shedding Light on Deep-Sea Biodiversity—A Highly Vulnerable Habitat in the Face of Anthropogenic Change - Paulus, Eva (Frontiers in Marine Science, 2021)
The deep sea is the most extensive habitat on our planet, and it supports surprisingly high biodiversity. With a multitude of different environments and conditions previously thought to be inhabitable, it is unclear how such high diversity was able to develop, but habitat heterogeneity and nutrient flux are certainly important factors to consider. In this review, the different methodologies used to examine biodiversity in the remote depths of the oceans are considered. In addition, the different environments in which biodiversity is studied are presented, and the various hypotheses on how high biodiversity is possible are examined. Unfortunately, this diversity is threatened by human impact similarly to shallow waters, and future endeavors such as deep-sea mineral extraction must be considered as a major threat to the environment. Many mysteries persist in the deep sea, but it is certain that threats such as overfishing, plastic pollution, and changes in ocean chemistry due to climate change are impacting even the most remote places in the oceans. It remains uncertain whether the deep sea is resilient toward anthropogenic disturbances, yet this is difficult to research on short timescales. There is little hope for areas in which exploitation, such as deep-sea mining, will be directly impacting the benthos and proper regulations are required to preserve biodiversity in the deep sea.